Financial Condition as a Moderator of Tax Awareness and Tri Nga Teaching on Tax Compliance Intention of MSMEs - Puspawati, Rista Arum; Prastyatini, Sri Lestari Yuli (International Journal of Economics Development Research (IJEDR), 2025)
This study aims to analyze the effect of tax awareness and tamansiswa tri nga teachings (ngerti, ngrasa, nglakoni) on taxpayer compliance intentions, with financial condition as a moderating variable. A quantitative approach was used by distributing questionnaires to individual taxpayers. The results showed that tax awareness and internalization of tri nga values had a positive effect on compliance intention. The values of ngerti (understanding), ngrasa (caring), and nglakoni (practicing) strengthen the moral integrity of taxpayers in fulfilling tax obligations. However, financial conditions proved to moderate the relationship: when financial conditions deteriorate, compliance intention decreases despite high awareness and moral values. The findings confirm the importance of a holistic approach to improving tax compliance, combining values education and supportive economic policies. The implications of this study are relevant for the formulation of value-based and welfare-based tax compliance improvement strategies.